Blood bacterial microbiota of the Texas tortoise, Gopherus berlandieri, in Tamaulipas, Mexico - Eduardo Manolo Medrano-Zapata; Jorge Luis Becerra-López; Pedro Almaguer-Sierra; Cristina García-De la Peña; Ludivina Barrientos-Lozano; Juan Flores-Gracia; Karen Berenice Lara-Rodríguez; Felipe Vaca-Paniagua; Clara E. Díaz-Velásquez; Aldo H. De la Cruz-Montoya (Revista Mexicana de Biodiversidad)
The blood bacterial microbiota of the Texas tortoise (Gopherus berlandieri) in Tamaulipas, Mexico, was characterized by next-generation sequencing. In 2019, blood was collected from 6 free-living tortoises. DNA was extracted, the V3-V4 region of the 16S rRNA gene was amplified, and Illumina sequencing was performed. The results showed 9 phyla, 20 classes, 42 orders, 81 families, 176 genera and 299 bacterial species. Firmicutes was the most abundant phylum in the blood of G. berlandieri; this taxon has been recorded as predominant in the intestine, excrement, nasal exudates and saliva of other species of the genus Gopherus. The dominant bacterial genera were Caldalkalibacillus, Anaerobacillus, Nesterenkonia and Bacillus. These taxa have been recorded in alkaline and halophilic soils, such as those found in G. berlandieri burrows. All of these bacterial taxa can enter the bloodstream of G. berlandieri via intestinal, oral and nasal translocation. Likewise, 3 bacterial taxa (Coxiella sp., Ehrlichia sp. and Anaplasma phagocytophilum) that are transmitted by arthropod vectors, as well as the potentially pathogenic Salmonella enterica were recorded. This information is the first bacteriological reference for the blood of G. berlandieri, and is expected to be useful for health and conservation programs.